Expansions in Maternity Leave Coverage and Mothers’ Labor Market Outcomes after Childbirth - Schönberg, Uta; Ludsteck, Johannes (Journal of Labor Economics, 2014)
This article analyzes the impact of five major expansions in maternity leave coverage in Germany on mothers’ labor market outcomes after childbirth. To identify the causal impact of the reforms, we use a difference-in-difference design that compares labor market outcomes of mothers who give birth shortly before and shortly after a change in maternity leave legislation in years of policy changes and years when no changes have taken place. Each expansion in leave coverage reduced mothers’ postbirth employment rates in the short run. The longer-run effects of the expansions on mothers’ postbirth labor market outcomes are, however, small.